Publishing & the Book in Africa: A Literature Review for 2018 - Zell, Hans (My University, 2019)
All the records in the four annual literature reviews thus far published are scheduled to be integrated into the online database of Publishing, Books & Reading in Sub-Saharan Africa. Unfortunately, access to the database remains temporarily unavailable. It is currently still in the process of being relaunched by its new host institution, Kwara State University Library in Nigeria (and see also the 2015 press release at http://www.hanszell.co.uk/Site/PDFs/Press%20release.pdf) Due to a number of persistent technical problems relating to metadata mapping and software functionality, as well as ongoing software development and data transfer issues, there have been serious delays in the migration of the database. However, the new hosts hope that remaining problems and issues can now be resolved shortly, and that they will be able to relaunch the database sometime early in 2019 on a more dynamic, Drupal-based open source content management platform. The first batch of updates and over 500 entirely new records will then also be added to the database. Meantime the accompanying collection of books, monograph series, journals, articles, and other documents on publishing and book development in Sub-Saharan Africa, from 1996 to 2014, donated by Hans Zell to Kwara State University Library in 2015 is now accessible at the recipient library. This is a continuation of an earlier collection and archive (for the 1960-1995 period) that was donated to the African Publishers Network/APNET in Harare in 1995. The 1996-2014 collection has now been fully catalogued and records have been created for each item and integrated in KWASU’s Online Public Access Catalogue (OPAC). A complete listing and inventory of the collection (which includes unpublished and archival material) can be found at http://kwasu.edu.ng/library/pbrssa.html. This page also includes a user guide, and an online form to register for access to and use of the collection. Access is free to any bona fide scholar or researcher from around the globe. For more information about the status of the new database, or access to the physical collection, contact Teslim B. Balogun, Project Director, PB&RSSA, Kwara State University Library, PMB 1530, Malete, Kwara State, Nigeria. Email: teslim.balogun@kwasu.edu.ng
Keywords: Africa; Bibliography; Book history; Publishing and book industries; Reference; Scholarly communication